The Legality of Intervention for Protection of National Abroad In Order To Solve Piracy and Hostage (A Study of Law Concerning the Possible Use of Armed Force to Release Hostages Detained by Abu Sayyaf Armed Group) - Syofyan, Syofirman (Indonesian Journal of International Law, 2017)
Until now hijacking or taking crew as hostage including the people who have Indonesian nationality has been repeatedly done by a group of suspected Abu Sayyaf rebel group. The use of non-violent efforts as negotiations have been conducted. There were failure and it resulted in the execution of the hostages. But some of them were successful to release the hostages allegedly after approving the fulfillment of the demands of the hostage-takers i.e. paying the ransom. However this did not stop the subsequent hostage-taking incident. This is clearly an injury for the country of origin of the crew or people who are taken hostage. When the non-violent efforts failed to stop acts of piracy and hostage then the use of force is logically expected to be used for such purposes. Yet international law prohibits this intervention as contrary to Article 2 para 4 of the UN Charter and does not meet the criteria of Article 51 of the UN Charter. Despite that this intervention can still be legalized if they meet the concept of R to P which can be adjusted or modified with this intervention and it is accepted by the people of ASEAN. Besides that these interventions also fulfill the qualification of necessity and proportionality.